PENGARUH PENAMBAHAN NATRIUM BISULFIT DAN PENCUCIAN ETANOL BERTINGKAT TERHADAP KUALITAS TEPUNG PORANG (Amorphophallus muelleri Blume) - Gunawan Pasaribu; Totok K. Waluyo; Novitri Hastuti; Gustan Pari; Emma Sahara (BRIN Publishing, 2016)
Porang (Amorphophallus muelleri Blume) is an alternative food sources from forest. Porang grows under forest canopy and potentially developed to improve food security. Naturally harvested porang contains high oxalate and less glucomannan. This paper observes possible quality improvement of porang flour in term of whiteness and glucomannan content. Porang collected from Nganjuk, East Java was quality tested and mixed with natrium bisulfite then rinse in ethanol repetitively. Results showed that the addition of sodium bisulfite improved the whiteness of porang flour for about 6.59%. Ethanol dehydration proces was able to improve glucomannan content from 12.86% to 38.11%. Fe and Ca content of mixed porang flour showed no significant difference. Porang flour from Nganjuk contained of 1,6-AnhydroBeta-D-Glucopyranose; 1,2,3,4-Cyclopentanetetrol,(1.alpha., 2.beta., 3.beta., 4.alpha.); cyclopropyl carbinol; aceticacid(CAS)ethylicacid; and hexadecanoic acid.